THE INFLUENCE OF SERVICE QUALITY AND HEALTH FACILITIES ON PATIENT SATISFACTION - Pratama, Ryan Martin; Purnamasari, Pupung; Yuniarti, Lelly (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Patient satisfaction with dental and oral health services is the key to the sustainability of a Dental and Oral Hospital (Rumah Sakit Gigi dan Mulut/RSGM). An important factor that can support patient satisfaction is the quality of services and health facilities available. The Dental and Oral Teaching Hospital has the potential to raise many views on the quality of services provided. One of the educational RSGMs that is frequently visited is the RSGM Universitas Padjadjaran (UNPAD). This study aims to examine and analyze the influence of service quality and health facilities on patient satisfaction of co-assistant young dentists at RSGM UNPAD. The type of research used is descriptive verification with a quantitative approach and survey method. The subjects of this research were patients treated by young co-assistant dentists at RSGM UNPAD, with a sample size of 135 respondents. Data were analyzed using SEM PLS. The results of the study showed that service quality had no effect on patient satisfaction, health facilities had an effect on patient satisfaction, and service quality and health facilities simultaneously had an effect on patient satisfaction of young co-assistant dentists at RSGM UNPAD. The findings of this research have the impact that the management of RSGM UNPAD needs to evaluate and improve the quality of service in the form of financing, facilities in the form of vehicle parking space capacity, and the level of satisfaction in the form of a more up-to-date reservation system.Keywords: Health Facilities, Service Quality, Patient Satisfaction